2014
DOI: 10.3389/fpsyg.2014.01169
|View full text |Cite
|
Sign up to set email alerts
|

The phonological and visual basis of developmental dyslexia in Brazilian Portuguese reading children

Abstract: Evidence from opaque languages suggests that visual attention processing abilities in addition to phonological skills may act as cognitive underpinnings of developmental dyslexia. We explored the role of these two cognitive abilities on reading fluency in Brazilian Portuguese, a more transparent orthography than French or English. Sixty-six children with developmental dyslexia and normal Brazilian Portuguese children participated. They were administered three tasks of phonological skills (phoneme identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 73 publications
5
58
0
15
Order By: Relevance
“…http://dx.doi. org/10.1038/nrn3836-c1 (2015)) 2 , Lobier and Valdois bring together 12 of their studies to argue that a visual attention (VA) span deficit meets the criteria that are required to demonstrate causality in developmental dyslexia [3][4][5][6][7][8][9][10][11][12][13][14] . Unfortunately, all of the studies that were discussed used letters to assess VA span; thus, the demonstrated deficit only affects letters and is causally ambiguous , as the individuals with dyslexia and control individuals that were studied differed dramatically in their experience of recoding letters to sound.…”
mentioning
confidence: 99%
“…http://dx.doi. org/10.1038/nrn3836-c1 (2015)) 2 , Lobier and Valdois bring together 12 of their studies to argue that a visual attention (VA) span deficit meets the criteria that are required to demonstrate causality in developmental dyslexia [3][4][5][6][7][8][9][10][11][12][13][14] . Unfortunately, all of the studies that were discussed used letters to assess VA span; thus, the demonstrated deficit only affects letters and is causally ambiguous , as the individuals with dyslexia and control individuals that were studied differed dramatically in their experience of recoding letters to sound.…”
mentioning
confidence: 99%
“…The identification and manipulation skills of phonemes are considered as complex, since the student is required to perform two operations. Besides demanding greater attention to the stimulus, the student must retain and execute the requested instruction, organize and plan the response, besides retrieving the information stored for some time in his/her memory 25,[34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…When considering ADHD diagnosis, it becomes important to highlight the factors which interfere in the metalinguistic tasks performance, such as attention deficit, behavioral maladaptation, difficulties in following instructions and the necessity of longer periods to complete tasks 30,35 .…”
mentioning
confidence: 99%
“…As PROLEC são amplamente utilizadas na clínica fonoaudiológica e na psicopedagógica para o rastreio de distúrbios específi -cos de aprendizagem, em especial a dislexia, e também como um guia para orientar programas de recuperação. Além dessa utilidade clínica, segundo seus autores, é também recomendada para pesquisadores da área da saúde e da educação, sendo já utilizada em diferentes estudos (Germano, Reilhac, Capellini, & Valdois, 2014;Macedo, Santos, Oliveira, & Martins-Reis, 2015;Machado & Almeida, 2014;Nalom, Soares, & Cárnio, 2015).…”
Section: Prolec-t -Prova De Compreensão De Texto: Análise De Suas Carunclassified